Pulso, suor, presença & teatro: reflexões de jovens escritores (Programa de Pós-Graduação em Artes - PPGArtes/UFPA, 2023)
Vários autores: Sarah Prazeres, Thalia Santos, Karina Diaz, Vanessa Lisboa, Claudio Raposo, Neire Conceição Nunes Lopes, Sidiane Nunes, Isabella Valentina, Marya Clara, Tertuliana Lopes, Rapha Rodrigues, Bella Duarte, Jerry Santos, Lucas Alberto da Cunha, Ana Luiza Aragão, Rick Brandão, Matheus Amorim.